Iraqi-Turkish Relations since 2003 and its Prospects: international and political journal - Khudhair, Asst. Lec. Husam Mohammed (The International and Political Journal, 2024)
Turkey began to look at the surrounding area differently than it did before 2002. Since the Justice and Development Party came to power in the country, Turkish foreign policy began to work towards forming friendly relations with neighbouring countries after the Justice and Development party adopted the principle of “zeroing problems”. It is natural for Iraq to be one of the priorities of the ruling authority in Turkey, as Iraq is very important for the Turks in terms of regional neighbourhood and market for the exchange of Turkish goods and products, as well as cultural, religious and ethnic ties that link the two countries. However, it is difficult to say that the Iraqi-Turkish relations have been free of tensions and escalation over time. This is due to several factors, perhaps the most prominent of which is the weakness of the governments that have ruled Iraq since 2003 and the regional and international pressures that are exerted against these governments. Bilateral relations between Iraq and Turkey have often been characterized by a lack of seriousness and stability, especially considering the existence of problems still pending to this day, such as the Kurdish issue, the water crisis, the security file, and others.